Plant polyphenols as natural drugs for the management of Down syndrome and related disorders. (December 2016) - Vacca, Rosa Anna; Valenti, Daniela; Caccamese, Salvatore; Daglia, Maria; Braidy, Nady; Nabavi, Seyed Mohammad
Highlights: Mitochondrial dysfunctions and oxidative stress are hallmarks in DS and in ID-related diseases. Polyphenols improve signalling pathways impaired in DS. Polyphenols target mitochondria and reduce oxidative stress. Polyphenols can suppress neuroinflammation and enhance memory and cognitive behaviour. Dietary polyphenols may be a therapeutic supplementation for DS handling. Abstract: Polyphenols are secondary metabolites of plants largely found in fruits, vegetables, cereals and beverages, and therefore represent important constituents of the human diet. Increasing studies have demonstrated the potential beneficial effects of polyphenols on human health. Extensive reviews have discussed the protective effects of polyphenols against a series of diseases such as cancer, cardiovascular diseases, diabetes, and neurodegenerative disorders. Limited studies have investigated the potential therapeutic effects of these natural compounds on neurodevelopmental disorders associated with intellectual disability, such as Down syndrome (DS), for which mitochondrial dysfunctions and oxidative stress are hallmarks and contribute to the deleterious symptoms and cognitive decline. This review, starting from the structure, source, bioavailability and pharmacokinetics of relevant polyphenols, highlights recent studies on the effect and potential molecular mechanism(s) of action of the phenolic compounds epigallocatechin-3-gallate, resveratrol and hydroxytyrosol in restoring mitochondrial energy deficit and in reversing phenotypical alteration in DS. The clinical implications of plant polyphenol dietary supplements as therapeutic tools in managing DS and other intellectual disability-related diseases, is also discussed.